There Is More Than One Kind of Extinction Learning - Goodman, Jarid; Packard, Mark G. (Frontiers in Systems Neuroscience, 2019)
The view that different kinds of memory are mediated by dissociable neural systems has received extensive experimental support. Dissociations between memory systems are usually observed during initial acquisition, consolidation, and retrieval of memory, however increasing evidence also indicates a role for multiple memory systems in extinction behavior. The present paper reviews a recent series of maze learning experiments that provide evidence for a multiple memory systems approach to extinction learning and memory. Evidence is described indicating that (1) the hippocampus and dorsolateral striatum (DLS) mediate different kinds of extinction learning, (2) the effectiveness of different extinction protocols depends on the kind of memory being extinguished, and (3) whether a neural system is involved in extinction is also determined by the extinction protocol and kind of memory undergoing extinction. Based on these findings, a novel hypothetical model regarding the role of multiple memory systems in extinction is presented. In addition, the relevance of this multiple memory systems approach to other learning paradigms involving extinction (i.e. extinction of conditioned fear) and for treating human psychopathologies characterized by maladaptive memories (e.g. drug addiction and relapse) is briefly considered.